Benefits of incorporating point of care ultrasound in the anaesthetic management of a dog requiring surgical correction of traumatic zygomatic fracture causing pseudoankylosis and severe dental malocclusion. Issue 2 (26th February 2022) - Phillips, Victoria; Ferreira, Jacques
Abstract: A 1‐year‐old male lurcher, weighing 19.5 kg, required general anaesthesia for correction of pseudoankylosis of the left temporomandibular joint. Severe left‐sided maxillomandibular and nasal deviation resulting in dental malocclusion was present with subsequent bilateral masseter muscle atrophy. Retrograde intubation was successfully performed using point of care ultrasonography to confirm percutaneous introduction of a catheter and vascular guide wire in the tracheal lumen which, when advanced rostrally, exiting the mouth via an occlusal gap, allowed 'railroading' of an armoured endotracheal tube into the extrathoracic trachea. A state of light general anaesthesia was maintained using total intravenous anaesthesia with propofol and medetomidine continuous rate infusions. Complete anti‐nociception provided by ultrasound‐guided trigeminal nerve blockade using bupivacaine was performed. Surgery restored sufficient range of motion to the temporomandibular joint permitting opening of the mouth. Recovery from anaesthesia was uneventful, and µ‐opioid analgesia was only required 18 hours after termination of surgery.